2017
DOI: 10.18632/oncotarget.22359
|View full text |Cite
|
Sign up to set email alerts
|

miR-1271 inhibits ERα expression and confers letrozole resistance in breast cancer

Abstract: Attenuation of estrogen receptor α (ERα) expression via unknown mechanism(s) is a hallmark of endocrine-resistant breast cancer (BCa) progression. Here, we report that miR-1271 was significantly down-regulated in letrozole-resistant BCa tissues and in letrozole-resistant BCa cells. miR-1271 directly targeted the chromatin of DNA damage-inducible transcript 3 (DDIT3) gene. miR-1271 expression level was inversely correlated to DDIT3 mRNA level in BCa biopsies. Form a mechanistic standpoint, reintroduction of exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Moreover, adjacent normal breast tissues sampled at least 5 cm from primary tumors were obtained from 12 chemotherapy-naive BCa patients during mastectomy, and were used as controls. The clinical characteristics of BCa patients recruited in the current study was categorized according to the St. Gallen standards [14] and summarized in S1 Table.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, adjacent normal breast tissues sampled at least 5 cm from primary tumors were obtained from 12 chemotherapy-naive BCa patients during mastectomy, and were used as controls. The clinical characteristics of BCa patients recruited in the current study was categorized according to the St. Gallen standards [14] and summarized in S1 Table.…”
Section: Methodsmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) primers used for different targets were listed in S2 Table. Subsequent quantitative reverse transcription PCR (RT-qPCR) was performed using QuantiFast one-step SYBR Green RT-PCR kit in Applied Biosystems 7300 Real-Time PCR System (Foster City, CA), as described in our previous work [14]. 18S served as the internal control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that the impact of miR-1271 on the tumor is getting more and more attention. Many studies have found that miR-1271 has a wide range of tumor suppressor effects ( 18 20 ). MiR-1271 is down-regulated in many human tumors and is involved in the inhibition of tumor epithelial-mesenchymal transition (EMT), induction of apoptosis, and reversal of chemo-resistance ( 18 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-27a and miR-125a-3p sensitize breast cancer cells to endocrine therapy [77,78]. On the other hand, miR-1271 participates in letrozole resistance through the inhibition of ERα expression [79]. Finally, the ERα/miR-124/AKT2 axis is involved in the pathogenesis of breast cancer [80].…”
Section: Mirnas and Er Function In Cancersmentioning
confidence: 99%